2010
DOI: 10.1097/mph.0b013e3181cb49a8
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Life-threatening Candida Peritonitis in a Child With Abdominal Non-Hodgkin Lymphoma Using Efungumab and Amphotericin B Colloid Dispersion

Abstract: Invasive fungal infections are serious complications of cancer therapy. We present a case report of a 12-year-old boy diagnosed with abdominal non-Hodgkin lymphoma and fecal and Candida peritonitis during induction chemotherapy. The invasive mycosis was managed using a combined approach of systemic antifungal agents including efungumab and surgical interventions. Efungumab, a recombinant antibody that inhibits extracellular heat shock protein 90, was used in combination with amphotericin B colloid dispersion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Efungumab binds to the middle region of HSP 90, preventing communication between the terminal regions, hence preventing necessary conformational changes . In addition to promising data from preclinical investigations and patient case reports with efungumab, a randomised, double‐blinded trial in patients with culture‐confirmed invasive candidiasis, compared L‐AmB or ABLC alone with L‐AmB or ABLC in combination with efungumab . The primary outcome, the composite of complete clinical response and mycological clearance on day 10, favoured combination therapy (84 vs. 48%, P < 0.001).…”
Section: Investigational Antifungal Agents and Vaccines No Longer In mentioning
confidence: 99%
See 1 more Smart Citation
“…Efungumab binds to the middle region of HSP 90, preventing communication between the terminal regions, hence preventing necessary conformational changes . In addition to promising data from preclinical investigations and patient case reports with efungumab, a randomised, double‐blinded trial in patients with culture‐confirmed invasive candidiasis, compared L‐AmB or ABLC alone with L‐AmB or ABLC in combination with efungumab . The primary outcome, the composite of complete clinical response and mycological clearance on day 10, favoured combination therapy (84 vs. 48%, P < 0.001).…”
Section: Investigational Antifungal Agents and Vaccines No Longer In mentioning
confidence: 99%
“…29 In addition to promising data from preclinical investigations and patient case reports with efungumab, a randomised, double-blinded trial in patients with culture-confirmed invasive candidiasis, compared L-AmB or ABLC alone with L-AmB or ABLC in combination with efungumab. [32][33][34][105][106][107][108] The primary outcome, the composite of complete clinical response and mycological clearance on day 10, favoured combination therapy (84 vs. 48%, P < 0.001). The rate of mycological clearance was more than twice as fast with efungumab and mycological resolution was achieved in 89% of the combination therapy group compared with 54% in the amphotericin group at day 10 (P < 0.001).…”
Section: Efungumabmentioning
confidence: 99%
“…In another study, a human recombinant MAb to heat shock protein 90 was used in the treatment of patients with invasive candidiasis (Pachl et al, 2006). Recently, Krenova et al (2010) reported the successful treatment of life-threatening Candida peritonitis in a child with abdominal non-Hodgkin lymphoma using a MAb against heat shock protein 90 in association with amphotericin B.…”
Section: Therapeutic Monoclonal Antibodies and Fungal Infectionmentioning
confidence: 99%
“…These very promising results have attracted the attention of the scientific community, and some case reports have been published on the use of antifungal agents in combination with Mycograb for treatment of severe, also pediatric, cases of disseminated C. albicans infections [4749]. …”
Section: Introductionmentioning
confidence: 99%